CB‐103: A novel CSL‐NICD inhibitor for the treatment of NOTCH‐driven T‐cell acute lymphoblastic leukemia: A case report of complete clinical response in a patient with relapsed and refractory T‐ALL. Issue 3 (16th June 2022) - Medinger, Michael; Junker, Till; Heim, Dominik; Tzankov, Alexandar; Jermann, Philip M.; Bobadilla, Maria; Vigolo, Michele; Lehal, Rajwinder; Vogl, Florian D.; Bauer, Michael; Passweg, Jakob
Abstract: Relapsed T cell acute lymphoblastic leukaemia (T‐ALL) has a very poor prognosis. A 24‐year‐old patient with relapsed high‐risk T‐ALL (PTEN gene deletion; NOTCH1 mutation), was treated with the NOTCH inhibitor CB‐103. Within 1 week of starting CB‐103, the bone marrow was free of T‐ALL blast infiltration (MRD+) and successfully underwent allogeneic hematopoietic stem cell transplantation (allo‐HSCT). Sequential samples of ctDNA to monitor the disease after allo‐HSCT showed a decrease of circulating Notch1 and PTEN alterations. This is the first T‐ALL patient treated with CB‐103. The observed clinical response encourages further exploration of CB‐103 in ALL.